The Philosophy of Charles W. Mills : Race and the Relations of Power - Westmoreland, Mark William, 1983-; Yancy, George (New York : Routledge, 2025)
Charles W. Mills (1951-2021) was considered by many to be the most well-known philosopher specializing in political philosophy and critical philosophy of race. This is the first collection of essays to critically examine the key themes of Mills's philosophy across his major works. The chapters in this volume engage with major themes such as the racial contract, non-ideal theory, metaphysics of race, epistemology of ignorance, and corrective justice. They also explore Mills's engagement with philosophical figures including Frederick Douglass, W. E. B. Du Bois, Maria Lugones, Immanuel Kant, Karl Marx, and John Rawls. Furthermore, the contributors seek to uncover unexplored terrain which may be illuminated by applying many of Mills's key insights. The Philosophy of Charles W. Millswill be of interest to scholars and advanced students working in political philosophy, philosophy of race, Africana philosophy, and Black political thought.
ForewordGeorge YancyIntroductionMark William Westmoreland1. Diagnosing White Aphasia: Mills and Domination ContractMark William Westmoreland2. Curdled Contracts: Reading Millsthrough a Lugonesian SpiritTaylor Rogers3. Corresponding Contracts: The Intersectional MillsCorey Reed4. Toward the Bourgeois Revolution: Situating Mills's Liberal TurnRafael Vizcaíno5. Mills on Class in Relation to RaceLawrence Blum6. Mills, Contracts, and the Limits of LiberalismClevis Headley7. A Page of History: Mills's Black Radical Kantianism and American Legal (Racial) RealismTimothy J. Golden8. Building (Conceptual) Bridges: Mills's Non-Ideal Theory and Disciplinary WhitopiasEmmalon Davis
Keywords: Mills, Charles W; Race relations -- Psychological aspects; Power (Philosophy); PHILOSOPHY / Political